Genetic abnormalities in Hereford cattle: the detection of vertical fiber hide defect and identification of quantitative trait loci associated with ocular squamous cell carcinoma - Upshaw, Katherine Ward (Kansas State University, 2021)
Genetic abnormalities often exist in opposition to an individual’s quality or length of life. Revealing prevalence and inheritance factors underlying these abnormalities is crucial for further understanding and management of these conditions. Vertical fiber hide defect is a genetic disorder that reduces collagen fiber interlacing and causes hides to tear during tanning, which increases cost and waste during leather good production. Hide biopsies were collected from 22 Hereford cattle, dyed with Masson’s trichrome stain, and histologically examined to ascertain if the condition could be detected in a modern herd of cattle. Although no samples expressed abnormal fiber orientation, the proposed novel histology approach was effective. Future research should incorporate additional samples from different herds and ancestry to help elucidate modern VFHD prevalence. Bovine ocular squamous cell carcinoma is the most common oncological neoplasm affecting cattle. It presents as ocular tumors, which can eventually metastasize into internal organs and contribute to carcass condemnation or reductions in lifetime productivity. The etiology of ocular squamous cell carcinoma is multifactorial, however prior literature suggests that it is genetically influenced. This experiment aimed to identify genomic regions associated with its expression. A total of 14 cases, 28 individual controls, and 10 control pools of 50 animals each was genotyped using an Illumina® BovineHD BeadChip and MANOVA-based association approaches revealed suggestively significant regions on chromosomes 6, 13, and 15 and one statistically significant region on chromosome 13. The expression of BOSCC appears to follow a polygenic mode of inheritance in which the small effects of many loci predispose cattle to developing the disease, however future research involving a greater number of samples is warranted. Both conditions pose substantial consequences for cattle producers and these experiments should aid in the prevention, detection, and control of these genetic abnormalities.
Keywords: Animal sciences; Genetics; Beef cattle; Vertical fiber hide defect (VFHD); Bovine ocular squamous cell carcinoma (BOSCC)